The reverse association between riboflavin intake and Helicobacter pylori infection in US adults: A cross-sectional study - Xinyu Xu; Peizhong Chen; Yingyi Li; Xiaoxuan Chen; Yunhui Yan; Zicheng Huang (PLoS ONE, 2025)
Objectives This study aimed to examine the association between dietary riboflavin (vitamin B2) intake and Helicobacter pylori infection prevalence among U.S. adults, addressing the growing interest in nutritional strategies for microbial pathogenesis modulation. Methods We analyzed data from 2,895 participants in the 1999–2000 National Health and Nutrition Examination Survey (NHANES) with complete dietary and H. pylori serology records. Multivariable logistic regression models adjusted for sociodemographic, clinical, and nutritional covariates were employed to assess riboflavin-infection relationships. Dose-response patterns were evaluated using restricted cubic splines, and subgroup analyses tested heterogeneity across population strata. Results The overall H. pylori seropositivity rate was 44.2%. Higher riboflavin intake exhibited a dose-dependent inverse association with infection risk. Compared to the lowest quartile (Q1 ≤ 1.13 mg/day), adjusted odds ratios (95% CI) for Q2 (1.14–1.64 mg/day), Q3 (1.65–2.34 mg/day), and Q4 (≥2.35 mg/day) were 0.77 (0.60–0.99), 0.63 (0.48–0.84), and 0.62 (0.41–0.94), respectively. Spline analysis confirmed a near-linear risk reduction with increasing intake. Conclusion These findings suggest that dietary riboflavin may inversely correlate with H. pylori infection in a dose-responsive manner, potentially mediated through mitochondrial function preservation, oxidative stress reduction, and gut microbiota modulation. While observational design precludes causal inference, the results underscore the need for prospective studies evaluating riboflavin’s role in infection prevention.